Exploring the Anti-Menopausal Potential of Rhizophora mucronata Lam. Ethanol Extract: A Comprehensive Study on Estrogen Receptor β Agonist Activity - Ernawati, Ernawati; Adam, Moh. Awaludin; Widiastuti, Irawati Mei; Insivitawati, Era; Nikmatullah, Muhammad; Riyadi, Putut Har; Azra, Mohamad Nor (Marine Science Department Diponegoro University, 2024)
Mangrove is a tropical forest that stores millions of benefits ecologically, biologically, and economically. Rhizophora fruit extract contained bioactive compounds components derived from natural ingredients and scientifically proven to have positive effects on health, among others, to prevent cancer, etc. This study aimed to investigate the potential of R. mucronata ethanol extract as an estrogen receptor β agonist for anti-menopausal purposes. Using a Completely Randomized Design (CRD), 25 mice were divided into five groups: a normal control group (NK), an ovariectomy control group (Ovx), and three ovariectomized groups (Ovx D1, D2, and D3) receiving different doses of the extract (200, 400, and 800 mg.kg-1 BW, respectively). The extract was administered orally, and various measurements were taken, including flavonoid content, using densitometry thin layer chromatography (TLC) and FTIR for functional group characterization. The study found a high rutin content (13.29%) in the fruit. Twelve compounds with potential estrogenic activity were identified, which were analyzed using SwissAdme software. Estradiol levels in serum increased with higher doses of the extract over four weeks. In silico and in vivo analysis showed 5 (five) selected compounds from the ethanol and ethyl acetate fractions with highest (most negative) to lowest binding affinity as candidates for anti-menopausal drugs. The administration of R. mucronata Lam. fruit extract in Ovx D1, Ovx D2 and Ovx D3 gave significantly different effects to each other on rat blood serum estradiol hormone levels. In this study, the dose 400 mg.L-1 BW rat gave P>5 increasing blood serum estradiol levels of ovariectomized rats.